PEMINATAN DAN LOYALITAS TERHADAP NIAT PEMBELIAN MENGGUNAKAN APLIKASI McDONALD’S INDONESIA ( Kegiatan Pengabdian Masyarakat ) : INTEREST AND LOYALTY ON PURCHASE INTENTION USING THE APPLICATION OF McDONALD'S INDONESIA (Community Service Activities) - I Gede Wiyasa (Jurnal Suara Pengabdian 45, 2022)
To win competition in business world, all businessman must have selling method effective efficiently in order to get right target and low east, to reach the target, the company should have same index parameter. To measure quality of service that be given to customer, many company try to implement service excellence, but fail, meanwhile the company is given out cost, time, power no so a little to do some training for his employees, what problem ?, actually, just giving training is not one solution because, familiarization, and manner to save customer is not so enough will be paradigm and skill for front line to save the customer, but seriously, high commitment at each of organization especially top management service excellence must be implemented in structural oriented at each of company.